2019
DOI: 10.14302/issn.2574-4488.jna-19-3112
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Relationship Between Advanced Oxidation end Products and Inflammatory Markers in Maintenance Hemodialysis Patients

Abstract: Introduction Increased oxidative stress and blunted anti-oxidant mechanisms are important problems in hemodialysis (HD) patients. Reactive oxygen species (ROS) act directly on proteins, leading to the formation of oxidized amino acids. Advanced oxidation protein products (AOPP) are among these substances. Many oxidant substances increase the level of AOPP. Iron is an element with strong oxidant capacity, especially when used intravenously. It is thought that iron treatment further increases the oxidative stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…The progression of DN, one of the biggest problems in nephrology field, pointing to that patients progress end-stage renal disease and require dialysis ( Aydin et al, 2019 ; Bacharaki et al, 2021 ) or kidney transplantation ( Webster et al, 2017 ; Jain et al, 2019 ; Van Sandwijk et al, 2019 ). Recent epidemiological studies reveal a link between Cd exposure and the incidence of diabetes and its complications ( Chen et al, 2006 ; Afridi et al, 2008 ; Akinloye et al, 2010 ; Satarug et al, 2010 ; Wallin et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The progression of DN, one of the biggest problems in nephrology field, pointing to that patients progress end-stage renal disease and require dialysis ( Aydin et al, 2019 ; Bacharaki et al, 2021 ) or kidney transplantation ( Webster et al, 2017 ; Jain et al, 2019 ; Van Sandwijk et al, 2019 ). Recent epidemiological studies reveal a link between Cd exposure and the incidence of diabetes and its complications ( Chen et al, 2006 ; Afridi et al, 2008 ; Akinloye et al, 2010 ; Satarug et al, 2010 ; Wallin et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The progression of CKD and renal fibrosis, one of the biggest issues in nephrology, indicated that patients inevitably progress ESRD and require dialysis or kidney transplantation ( Webster et al, 2017 ; Aydin et al, 2019 ; Van Sandwijk et al, 2019 ). Numerous studies have demonstrated that renal fibrosis was associated with the dysbiosis or dysregulation of gut microbiota, non-coding RNAs, renin–angiotensin system, aryl hydrocarbon receptor, IƙB/NF-ƙB, Keap1/Nrf2, TGF-β/Smad, and Wnt/β-catenin signaling pathways ( Ma et al, 2018a ; Chen et al, 2019b ; Garg and Maurya, 2019 ; Zhao et al, 2019 ; Hu et al, 2020a ; Miao et al, 2021b ; Wang et al, 2021d ; Wu et al, 2021 ; Zhou et al, 2021 ) as well as metabolite disorders including tryptophan metabolism and lipid metabolism ( Zhao, 2013a ; Zhao et al, 2015 ; Wang et al, 2019 ; Liu et al, 2021a ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, with the progression of CKD, it can easily lead to the occurrence of cardiovascular diseases ( Ravid et al, 2021 ). Renal fibrosis, characterized by tubulointerstitial fibrosis and glomerulosclerosis, is the common pathway and inevitable outcome of various progression of CKD to end-stage renal disease (ESRD) and need renal replacement treatments such as dialysis and transplantation ( Humphreys, 2018 ; Aydin et al, 2019 ; Jain et al, 2019 ; Carta et al, 2020 ; Sawhney and Gill, 2020 ). Regardless of the underlying diseases, it has been demonstrated that patient’s survival is associated with tubulointerstitial fibrosis ( Tampe and Zeisberg, 2014 ) and the extent of tubulointerstitial fibrosis on renal biopsy is thought as a prognostic indicator for CKD treatment ( Tang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%